Knowledge systems and adaptive collaborative management of natural resources in southern Cameroon : decision analysis of agrobiodiversity for forest-agriculture innovations - Mala, William Armand (Stellenbosch: University of Stellenbosch, 2009)
Thesis (PhD (Dept. of Forest and Wood Science))--University of Stellenbosch, 2009.